1988
DOI: 10.1139/g88-047
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes, C-banding, and chromosomal location of active nucleolar organizing regions in Tapinoma (Hymenoptera, Formicidae)

Abstract: The haploid and diploid karyotypes of Tapinoma erraticum (n = 8) and Tapinoma nigerrimum (n = 9) were analyzed using C-banding and observation of NOR sites. C-banding showed the existence of heterochromatin in the paracentromeric regions of all chromosomes. The analysis of NOR sites in these species proved the existence of primary activity NOR in one or two chromosomes, respectively, whereas the other chromosomes showed secondary activity NOR, expressed only in a minority of cells. In both species the NOR were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…In T. chanchamayoensis, a marked reaction was seen with DA/CMA 3 ( Figure 4A), while in T. recursa, the staining with CMA 3 revealed no GC-rich regions in the chromosomes ( Figure 4B). The positive reactions seen were probably associated with nucleolus organizing regions (NORs), as observed in 188 Costa et al other insects such as Orthoptera (Camacho et al, 1991), Coleoptera (Maffei et al, 2001), and in other Hymenoptera, including Formicidae (Palomeque et al, 1988;Imai et al, 1992), Sphecidae (Araújo et al, 2000) and Meliponini (Brito et al, 1999(Brito et al, , 2003Caixeiro, 1999;Rocha, 2000). Some authors have suggested that the number of NORs revealed by impregnation with silver nitrate or by CMA 3 staining is an important taxonomic character.…”
Section: Resultsmentioning
confidence: 73%
“…In T. chanchamayoensis, a marked reaction was seen with DA/CMA 3 ( Figure 4A), while in T. recursa, the staining with CMA 3 revealed no GC-rich regions in the chromosomes ( Figure 4B). The positive reactions seen were probably associated with nucleolus organizing regions (NORs), as observed in 188 Costa et al other insects such as Orthoptera (Camacho et al, 1991), Coleoptera (Maffei et al, 2001), and in other Hymenoptera, including Formicidae (Palomeque et al, 1988;Imai et al, 1992), Sphecidae (Araújo et al, 2000) and Meliponini (Brito et al, 1999(Brito et al, , 2003Caixeiro, 1999;Rocha, 2000). Some authors have suggested that the number of NORs revealed by impregnation with silver nitrate or by CMA 3 staining is an important taxonomic character.…”
Section: Resultsmentioning
confidence: 73%
“…NORs adjacent to C bands have also been observed in some insects (Palomeque et al, 1988;Rodríguez-Iñigo et al, 1992;Lorite et al, 1997;Souza et al, 1998). The mitotic metaphases of N. cruentata submitted to the base-specific fluorochromes DAPI/ MM and analyzed with DAPI filter have evidenced that the negative heteropycnotic regions in the chromosomic pairs 1, 2 and 3 do not posses highly repeated AT base sequences, since these regions are DAPI negative.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous article (Palomeque et al, 1988) we have reported the existence in Tapinoma nigerrimum of an Ag-positive region (or Ag-NOR) in chromosomes 6 and 8. Amongst the remaining chromosomes, the number of chromosomes bearing an Ag-positive region varied between individuals and populations.…”
Section: Introductionmentioning
confidence: 96%